Free higher education policy network viewed through power, cooperation and conflict in South Africa - Molokwane, Masibane John (My University, 2019)
The notion of policy networks is an integral instrument of policy-making in democratic states. Significant policy challenges are deemed often too complex to be dealt with only through traditional hierarchal government structures. The notion of policy networks is used to analyse and evaluate policy processes and their outcomes. The knowledge gap that the study is dealing with is on the role and effects the interplay of power, cooperation and conflict has in the policy networks and the policy-making process. The aim of this study was to explore the interplay between power, conflict and cooperation in the free higher education policy network in South Africa. A dialectical approach to analysis of policy networks was applied to inform the conceptual frame used in the study. The methodology followed the interpretivist-constructivist paradigm, which then informed the use of qualitative methods in the study. A snowballing sampling approach was employed to identify the study participants. The study analysed the results by using a thematic analysis approach. Findings in the study confirmed that free higher education policy-making was happening through a complex policy network. This free higher education network was characterised by a dominance of power, along with high levels of conflict and cooperation among actors who tended to share the same interests. The presence of power, conflict and cooperation had an influence on the network’s structure, interactions, context and the policy outcome. The influence of power, conflict and cooperation demonstrated that there is an iterative and dialectical relationship between network structure, interactions, context and policy outcome.
Thesis submitted to the Faculty of Commerce Law, and Management, School of Governance, University of Witwatersrand, in partial fulfilment of the requirements for the degree Master of Management in Public Policy (MMPP), Johannesburg, South Africa 2019
Keywords: Higher education and state; Education, Higher--Economic aspects--South Africa; State universities and colleges--South Africa